The Effect of Company Size, Financial Performance, and Corporate Governance on the Disclosure of Sustainability Report - Indrianingsih, Indrianingsih; Agustina, Linda (Universitas Negeri Semarang, 2020)
The purpose of this research is to analyze the effect of company size, profitability, leverage, liquidity, company activities, board directors, independent commissioners, and audit committee on sustainability report disclosure. The population of this research was non-financial companies listed on the IDX in 2013-2017 as many as 483 companies. The sample was selected using purposive sampling technique and obtained 17 samples with 5 years of observation so there were 85 units of analysis. Data collection technique used documentation technique. The analysis tool to test hypothesis was multiple linear regression analysis. The results show that variables of liquidity and audit committee have a positive effect on the sustainability report disclosure. Leverage has a negative effect on sustainability report disclosure. Meanwhile, company size, profitability, company activities, board of directors, and independent commissioners do not affect on sustainability report disclosure. The conclusion in this research is variables of leverage, liquidity, and audit committee can provide an important role in sustainability report disclosure. The suggestion for the next researcher is to pay attention to the calculation of corporate ratio, whether using net sales or gross sales.